Penyebaran Pemahaman Moderasi dalam Menangkal Paham Radikalisme di Pondok Pesantren Kabupaten Bantaeng: Mengukur Kontribusi Program Studi Perbandingan Madzhab dan Hukum - Idrus, Achmad Musyahid; Laman, Ilham; Asti, Mulham Jaki (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
This research wants to answer important questions related to the reality of students' understanding of moderation and radicalism, the role of the Comparative Madzhab and Law Study Program in integrating the school of jurisprudence towards the spread of religious moderation in warding off the dangers of radicalism. This question is motivated by the reality of the danger of radicalism caused by intolerance in madhab and Santri is the main pillar in building moderation and countering radicalism. Therefore, the significance of this research is to offer the importance of madhhab moderation as the initial door to achieve religious moderation and counteract radicalism among students. The method used in this research is a case study approach analyzed with the theory of tasyri philosophy. Data was collected by direct interviews with students of As'adiyah Dapoko Islamic Boarding School and DDI Mattoanging Islamic Boarding School, Bantaeng Regency as primary flat sources and religious and community leaders as secondary flat sources. The research findings are divisions in religion caused by madhhab fanaticism and chaos in the nation and state caused by radicalism. This study concludes that the school of jurisprudence can contribute to counteracting radicalism if it is well understood, the reality of students' understanding of moderation and radicalism is still low, understanding the wisdom of moderation law can strengthen religious moderation and understanding the dangers of radicalism can maintain benefits in religion and state.